2010
DOI: 10.1007/s12064-010-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

The balance between predictions and evidence and the search for universal macroecological patterns: taking Bergmann’s rule back to its endothermic origin

Abstract: Geographical variation in environmental temperatures is expected to impose clinal phenotypic selection that results in the expression of large-scale gradients of body mass variation within animal clades. Body size is predicted to increase with increasing latitude and elevation, and hence, with decreasing temperature, a pattern broadly known as Bergmann's rule. However, empirical observations are highly conflicting. Whilst most studies support this prediction in endotherms (birds and mammals), analyses conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 80 publications
(117 reference statements)
1
48
1
Order By: Relevance
“…Consequently, this theory assumes that female size increases with latitude and elevation, a pattern broadly known as Bergmann's rule. However, a number of studies reveal that this important assumption is consistently violated by empirical evidence in most lizards (Ashton and Feldman 2003;de Queiroz and Ashton 2004;Pincheira-Donoso 2010), including Liolaemus (Pincheira-Donoso et al 2007b, 2008a, where Bergmann's rule is not supported. Hence, as latitude and elevation increase, the potential for increased brood size is limited by constraints of thermal selection on body size, making this prediction unlikely despite the intuitive appeal of the mechanistic idea behind it.…”
Section: The Strength Of Fecundity Selectionmentioning
confidence: 99%
“…Consequently, this theory assumes that female size increases with latitude and elevation, a pattern broadly known as Bergmann's rule. However, a number of studies reveal that this important assumption is consistently violated by empirical evidence in most lizards (Ashton and Feldman 2003;de Queiroz and Ashton 2004;Pincheira-Donoso 2010), including Liolaemus (Pincheira-Donoso et al 2007b, 2008a, where Bergmann's rule is not supported. Hence, as latitude and elevation increase, the potential for increased brood size is limited by constraints of thermal selection on body size, making this prediction unlikely despite the intuitive appeal of the mechanistic idea behind it.…”
Section: The Strength Of Fecundity Selectionmentioning
confidence: 99%
“…Although well supported in birds and mammals (Hawkins and Diniz-Filho 2006, Rodríguez et al 2006, Olson et al 2009, Pincheira-Donoso 2010, the generality of Bergmann's rule is still questioned in ectotherms. Numerous studies have shown that many ectotherms also display clinal variation in body size (Mousseau 1997, Ashton 2002, Ashton and Feldman 2003, Cruz et al 2005, Pincheira-Donoso et al 2007, whereas others present conflicting results (Partridge and Coyne 1997, Arnett and Gotelli 1999, Belk and Houston 2002, de Queiroz and Ashton 2004.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern has been conjectured to also apply to ectotherms, through either the same mechanism or some alternative process (e.g. Ashton & Feldman, 2003;Adams & Church, 2008;Pincheira-Donoso et al, 2008;Pincheira-Donoso, 2010;Meiri, 2011). However, it remains unclear whether the body size of coldblooded animals actually responds to macroclimatic gradients as it does in endotherms.…”
Section: Introductionmentioning
confidence: 99%